DOMESTIC VIOLENCE: THE PERCEPTION THAT THE VICTMS HAVE OF THEIR PARTNER, THEIR RELATIONSHIP AND THE VIOLENCE CAUSES - Mirian Botelho Sagim; Zélia Maria Biasoli-Alves; Vanessa Delfino; Fabiola Perri Vanturini (Universidade Federal do Paraná, 2007)
Nowadays violence presents high visibility, and it is a subject that interests researchers from different areas whose aimis to understand its causes, related factors and consequences so that it can be possible to implement adequate intervention programs.The present research held through document review, objectified to analyze document contents (Police Reports) from Female DefensePolice Station (Goias State/ Brazil) - where domestic assault complaints are filed - in 2000. It aimed to describe the types of domesticassault against women, couples' relationship and abusers' characteristics. The results show an amount of 210 complaints of abuse,made by women, almost all of them married, with children, and working outside home; in accordance with their description, thepartner is violent and rude and his aggression is caused by jealousy or alcoholism. It is discussed not only women's perception on theassault they suffered but also its causes and their reasons why they do not forward a lawsuit.